(untitled) (Research, Society and Development, 2021)
Caprine breeding is a largely exploited activity in Brazil, with a herd of over 10 million goats concentrated mostly in the Northeast region, which contains 93.9% of the national herd. However, this region is affected by huge losses due to inappropriate management and illness occurrence, such as leptospirosis, a reproductive disease that causes economic and productive losses. Considering these previous statements, we aimed to determine the most frequent seroprevalence, serogroups and factors associated with the occurrence of leptospirosis in goats from different states and biomes of the Brazilian northeast and properly locate the disease throughout the region through the analysis of epidemiological questionnaires and geographic data. The samples were submitted to the Microscopic Agglutination Test (MAT) with a cutoff of 50. In addition, geographic data were analysed to create maps with epidemiological descriptions of the disease in the states. The total occurrence of seropositive animals was 19.93% (119/597), 18.92% (35/185) in the state of Alagoas and 20.38% (84/412) in Maranhão. The most common serogroups in these states were Autumnalis (31.09%) and Icterohaemorrhagiae (23.81%). Dividing the results, it was possible to observe a greater occurrence of the serogroup Autumnalis (42.86%) Icterohaemorrhagiae (28.57%) in the state of Alagoas, Caatinga biome, plus Autumnalis (26.19%) and Icterohaemorrhagiae (23.81%) in the state of Maranhão, Cerrado biome. It was proven that Leptospira sp. is present in both states and biomes analyzed, present in diverse areas as in vegetation and climate, warning preventive care towards the disease.